Mysterious Illnesses of Human Commodities in Woody Allen and Franz Kafka - Iris Bruce (Studies in 20th & 21st Century Literature, 1998)
The article examines correspondences between Woody Allen's film Zelig and texts by Franz Kafka. Both Leonard Zelig and Gregor Samsa (The Metamorphosis) suffer from mysterious illnesses which are multi-determined. Twentieth-century racial stereotypes are partially responsible for them; other causes lie in the commercialization of life in early twentieth-century society. Zelig's illness parallels the cultural trends and political movements of his time and becomes full-blown in the fascist movement. Zelig is therefore also a commentary on the cultural climate which helped bring about the rise of fascism. Kafka could not benefit from Allen's hindsight, but Kafka's representation of what turns human beings into commodities with no identity of their own nonetheless complements Allen's picture. Further parallels are drawn between Zelig and Kafka's hunger artist, the performing ape Rotpeter ("A Report to an Academy"), and Karl Rossmann (Amerika). All of these protagonists fail to retain a sense of selfhood in a commodified world. Yet the causes for their illnesses lie not in themselves but in society on the whole, and for this reason there is no cure for these human commodities. Unlike Kafka, though, Woody Allen grants Zelig a cure in the end, a cure which is possible only in the realm of fantasy.
Keywords: Woody Allen; film; Zelig; Franz Kafka; Leonard Zelig; Gregor Samsa; The Metamorphosis; mysterious illnesses; multi-determined; Twentieth-century; racial stereotypes; commercialization; illness; fascism; fascist movement; cultural climate; hindsight; commodities; human beings; identity; hunger artist; Rotpeter; A Report to an Academy; Karl Rossmann; Amerika; selfhood; commodified world; cure; society